Radiologic and clinical features of infection related cytotoxic lesions of corpus callosum splenium in adults - İkidağ, Mehmet Ali (Journal of Surgery and Medicine, 2021)
Background/Aim: The cytotoxic lesion of corpus callosum splenium (CLCCS) is a clinical-radiologic syndrome that typically manifests in children. It is characterized by restricted diffusion in the splenium of the corpus callosum on magnetic resonance imaging, and accompanying symptoms of encephalopathy. There are a few case reports regarding the adult population in the literature, and only a couple of these are related to febrile illness in adults. We aimed to evaluate the clinical and the radiologic characteristics of infections related to CLCCS in adults. Methods: For this case series study, we reviewed the MRI examinations that were performed in our hospital between 2014 and 2019 to identify cases with corpus callosum splenium lesions related with febrile diseases in adults. We excluded the cases with demyelinating diseases, trauma, arterial or venous occlusive diseases, metabolic-toxic diseases, and posterior reversible encephalopathy syndrome (PRES), patients who had alcohol or drug abuse, or known malignancies. The admission dates, symptoms within the prodromal period, physical and laboratory findings, electroencephalograms, MRI features, medications and patient outcomes were recorded. Corpus callosum involvement on MRI was classified as Type 1 if lesions were limited to splenium, and Type 2 if pericallosal white matter extension was present. Results: Seven patients (four males, three females, and ages ranging from 18 to 33 years with a mean of 26.4 years) were included in the study. All patients experienced prodromal symptoms such as fever (n=7), nausea (n=5), vomiting (n=4), diarrhea (n=4) and abdominal discomfort (n=3). Neurological symptoms included drowsiness (n=4), speech disorder (n=2), impairment of consciousness (n=4), lower extremity weakness (n=2), and seizures (n=1). Neurological examination revealed confusion (n=4), nuchal rigidity (n=2), and ataxia (n=2). In one patient, the blood culture was positive for Staphylococcus epidermidis, and the stool culture was positive for Enterococcus species. MRI findings of all patients revealed Type 1 oval (n=4) or round (n=3) shaped corpus callosum splenium lesions that appeared hyperintense on T2 and FLAIR images with diffusion restriction. None of our patients had band-like Type 1 or Type 2 lesions. Clinical relief was observed in 2 days in six patients, however, rapid clinical deterioration resulting in death occurred in one patient. Conclusion: The leading symptoms in adults are fever and gastrointestinal disturbances including, nausea, vomiting, and diarrhea, while neurological examinations mostly reveal confusion, nuchal rigidity, and ataxia. In adult patients, restricted diffusion on MRI is usually limited to splenium, and pericallosal white matter is usually not involved. Mostly encountered in autumn and winter, encephalitis/encephalopathy with diffusion restriction in the splenium of corpus callosum in an adult febrile patient usually has a good prognosis, although it may lead to severe outcomes, and even result with death. Clinicians should be aware that, if even Type 1, isolated corpus callosum diffusion restriction on MRI may has catastrophic results in a febrile patient. Further studies may be useful to delineate the mechanism and its relationship with higher bilirubin levels in patients with CLCCS.